2022
DOI: 10.1001/jamanetworkopen.2022.10331
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Surgery Preference and Receipt in Ductal Carcinoma In Situ After Breast Magnetic Resonance Imaging

Abstract: IMPORTANCEGuiding treatment decisions for women with ductal carcinoma in situ (DCIS) requires understanding patient preferences and the influence of preoperative magnetic resonance imaging (MRI) and surgeon recommendation. OBJECTIVE To identify factors associated with surgery preference and surgery receipt among a prospective cohort of women with newly diagnosed DCIS. DESIGN, SETTING, AND PARTICIPANTS A prospective cohort study was conducted at 75 participating institutions, including community practices and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…Third, we used multivariable logistic regression with Firth biasreducing penalized likelihood method. Different from conventional maximum likelihood estimation, the Firth log likelihood is penalized by the determinant of the information matrix, provides bias reduction for a small number of events, and yields finite and consistent estimates even in the case of separation (48)(49)(50)(51)(52)(53)(54)(55)(56)(57).…”
Section: Discussionmentioning
confidence: 99%
“…Third, we used multivariable logistic regression with Firth biasreducing penalized likelihood method. Different from conventional maximum likelihood estimation, the Firth log likelihood is penalized by the determinant of the information matrix, provides bias reduction for a small number of events, and yields finite and consistent estimates even in the case of separation (48)(49)(50)(51)(52)(53)(54)(55)(56)(57).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Fosh et al reported high levels of satisfaction in DCIS patients treated with partial mastectomy and OPS2 [ 32 ], and a recent study by Fazeli and colleagues interviewed 316 women with DCIS prior to surgery and found that 80% would have preferred wide local excision over mastectomy as a treatment of choice [ 33 ]. Our data suggests that breast-conserving surgery with OPS2 yields lower morbidity than conservative mastectomy, a finding that is in line with that reported by Livingston-Rosanoff and colleagues, who found that DCIS patients treated with mastectomy were more likely to report lower levels of satisfaction than patients treated with BCS [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of preoperative breast magnetic resonance imaging (MRI) in guiding the treatment of ductal carcinoma in situ (DCIS) diagnosed at core needle biopsy (CNB) or vacuum-assisted biopsy (VAB) is an open issue in clinical practice [ 1 4 ] that has been extensively investigated considering different outcomes, e.g., short-term surgical results [ 5 16 ], upgrade to invasive cancer at final pathology [ 17 , 18 ], detection of additional ipsilateral or contralateral disease [ 19 ], long-term recurrence [ 20 ], and patient preferences [ 21 , 22 ]. Surgical outcomes are crucial, as the rate of mastectomy and the rate of reoperation after breast-conserving surgery are major indicators of breast care quality and the focus of multidisciplinary efforts towards surgical de-escalation [ 23 25 ].…”
Section: Introductionmentioning
confidence: 99%